Growth Indices of Low and Normal Birth Weight of 2-5 year Old Children in Rural Areas of Gonbad , Iran - Abdol-Hamed; Behrooz Ebrahimzadehkor; Ata-Mohammad Dorri (Golestan University of Medical Sciences, 2015)
Background and Objective: Given the correlation of birth weight with growth indices, this study aimed at determing the growth indices of low birth weight (LBW) and normal birth weight of 2-5 year old children in rural areas of Gonbad, Iran. Material and Methods: In this retrospective cohort study, using multi-stage cluster sampling, 200 LBW 2-5-year-old children and 200 normal birth weight were selected. The data was collected through interview and analyzed by Pearson correlation, t-test and chi-square. Results: The prevalence of shorter stature and low weight-for-age in case group was higher than those of controls, and the high weight-for-age was higher in control group. Gestational age, maternal Body Mass Index (BMI), intepregnancy interval and age of delivery were determined as the most important factors related to LBW. Conclusion: The results imply that LBW affects adversely on growth indices in 2-5 year old children. Considering gestational age, maternal BMI, interpregnancy interval and age of delivery, we recommend recognizing the mothers who are at risk for delivery of LBW to educate and take care of them.